Pengaruh Pengendalian Internal Dan Moralitas Individu Terhadap Fraud Orderan Pada Jasa Transportasi Berbasis Online Go-Jek Di Kota Padang - Jana Haniful Khair; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2019)
This study is to study the effect of internal control and individual morality on fraudulent transportation orders based online at PT. Go-Jek, City of Padang. This research is quantitative research with primary data from questionnaires and using a Likert scale. The population of this research is a car and motorcycle driver, PT. Go-Jek in Padang City. The purposive sampling technique of sampling and a sample of 150 respondents. Data analysis technique is data quality test, classic assumption test and hypothesis test consisting of multiple linear regression tests using SPSS 23.0 for Windows. The results of this study indicate that internal control and individual morality have a negative and significant influence on order fraud